Between Taboo and Virtue: Islamohumorism in the Reconstruction of Muslim Identity and Piety through Social Media - Mulyawati, Husni (Universitas Islam Internasional Indonesia, 2023)
The discourse on the intersection between Islam and humor has evolved especially since 9/11, but is still considered a peripheral matter in Muslim societies. But comedians can be classified as organic intellectuals—as Gramsci contended—who take a particular role in social change. Rather than viewing humor as a counternarrative toward Islamophobia in Muslim minority countries, as many Western scholars have discussed, ‘Islamohumorism’ in Indonesia somehow shows a different type of polarization, with some Muslims considering humor as a taboo making fun of with religion, while others regard it simply as a means to relax and even evoke piety. This paper aims to showcase the conflicting responses toward Islamohumorism in Indonesia and the impact of these responses. Furthermore, this paper also attempts to examine how comedy frames Muslim identity and stimulates public piety. I focus on discussing three forms of comedy, namely stand-up comedy, exemplified by Dzawin Nur in his YouTube segment “Kuliah Antum”, crosshijaber parody conducted by @holaofadlan on Instagram, and memification in the @haram_house account on Instagram. This research utilizes qualitative methods based on observation and semi-in-depth interviews. By utilizing the uses and gratifications theory of Katz and Blumler (1974) as a framework, this paper portrays the impact of Islamohumorism on Indonesian Muslims through social media. I argue that humor is not inherently taboo and does not contradict Islamic principles. Instead, it serves as a quintessential narrative that critiques societal shortcomings and inequalities. Moreover, it has the potential to foster a sense of community, amplify Muslim identity, and even endorse piety. Nonetheless, it is essential to acknowledge that Islamohumorism can also contribute to the fragmentation of religious authority.